Ecotourism - Weaver, David (Milton, Qld. : Wiley, 2008)
This book reflects contemporary developments in the field. Building on the strengths of the first edition, the text discusses the significance of ecotourism in the domestic and international tourism sectors. The origins, markets, venues and impact of ecotourism form the basis of the first part of the book. Business aspects of ecotourism, external environments, organisations and policies are examined in the second part of the book, along with special environments, such as islands, polar regions and indigenous territories, and distinctive activities, such as whale-watching and penguin-watching. The management of ecotourism is covered comprehensively and is illustrated by extensive industry and destination examples derived mainly from the peer-reviewed literature. A highlight of the book is a regional survey of ecotourism that offers comparative insights into ecotourism in Australia, the South Pacific, Asia, Europe, the Americas and Africa.
Includes index and bibliographycal references
Keywords: Ecotourism